2010
DOI: 10.1159/000322811
|View full text |Cite
|
Sign up to set email alerts
|

Equine Disorders of Sexual Development in 17 Mares Including XX, <i>SRY</i>-Negative, XY, <i>SRY</i>-Negative and XY, <i>SRY</i>-Positive Genotypes

Abstract: We described the clinical, cytogenetic and molecular findings of 17 clinical equine cases presented for abnormal sexual development and infertility. Six horses with an enlarged clitoris had an XX, SRY-negative genotype, which displayed male-like behavior (adult individuals). Bilateral ovotestes were noted in 2 of those cases, while another case showed increased levels of circulating testosterone. Six horses with a female phenotype, including normal external genitalia, had an XY, SRY-negative genotype. These in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 105 publications
5
63
0
1
Order By: Relevance
“…Further studies investigating isozyme expression of 5α-reductases in other accessory sex glands are necessary to determine the patterns and relative levels in the male reproductive tract of the horse. This information may help in distinguishing among or interpreting the phenotypes and genetic defects associated with male pseudohermaphroditism in horses, which have been far less extensively described or properly characterized (Lear & McGee 2012) than have karyotypic abnormalities or cases of sex reversal (Villagomez et al 2011. Defects in the androgen receptor gene associated with suspected androgen insensitivity syndrome have been reported in stallions (Revay et al 2012), which presumably lack mesonephric duct-derived tubular or glandular accessory tissue, although phenotypes remain poorly defined with respect to internal genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies investigating isozyme expression of 5α-reductases in other accessory sex glands are necessary to determine the patterns and relative levels in the male reproductive tract of the horse. This information may help in distinguishing among or interpreting the phenotypes and genetic defects associated with male pseudohermaphroditism in horses, which have been far less extensively described or properly characterized (Lear & McGee 2012) than have karyotypic abnormalities or cases of sex reversal (Villagomez et al 2011. Defects in the androgen receptor gene associated with suspected androgen insensitivity syndrome have been reported in stallions (Revay et al 2012), which presumably lack mesonephric duct-derived tubular or glandular accessory tissue, although phenotypes remain poorly defined with respect to internal genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…Where testing was possible, all reported cases have been SRY -negative by Southern blotting, PCR, RFLP, or FISH ( fig. 2 B) [Milliken et al, 1995;Pailhoux et al, 1995;Meyers-Wallen et al, 1997;Abe et al, 1999;Buoen et al, 2000;Vaughan et al, 2001;Bannasch et al, 2007;Jaszczak, 2010;Villagómez et al, 2011]. Some horses may display male behaviors including filly herding, teasing, biting, and mounting due to increased levels of testosterone from testicular tissue.…”
Section: Dsd In Horsementioning
confidence: 99%
“…[ Bannasch et al, 2007] [ Raudsepp et al, 2010] [ McGee, 2011] [ Bowling et al, 1987] Arabian Andalusian Quarter Horse Appaloosa Arabian [Miyake et al, 1979;Halnan, 1985;Bowling et al, 1987;Paget et al, 2001] [ Buoen et al, 2000;Villagomez et al, 2011] [ Raudsepp et al, 2010;Villagomez et al, 2011] [ Raudsepp et al, 2010] [ Kent et al, 1986;Bowling et al, 1987;Kent et al, 1988] Half-bred Anglo-Arabian Appaloosa Standardbred Mixed Warmblood Morgan [Bugno et al, 2007] [ Buoen et al, 2000] [ Pailhoux et al, 1995;Mäkinen et al, 1999;Makinen et al, 2001;Raudsepp et al, 2010;Villagomez et al, 2011] [ Raudsepp et al, 2010] [ Bowling et al, 1987] Half-Arabian Arabian Thoroughbred Oldenburg Pasa Fino [Gill et al, 1988] [ Buoen et al, 2000;Villagomez et al, 2011] [ Abe et al, 1999;Bugno et al, 2003;Raudsepp et al, 2010;Villagomez et al, 2011] [ Kuiper et al, 2010] [ Kent et al, 1986;Kent et al, 1988] Clydesdale Belgian Quarter Horse Quarter Horse [Klunder et al, 1990] [ Villagomez et al, 2011] [ Raudsepp et al, 2010;Villagomez et al, 2011] [ Kent et al, 1986;Bowling et al, 1987;Kent et al, 1988] Fjord Konik Polski Sta...…”
mentioning
confidence: 99%
“…In 4 cases, mares with this condition exhibited hypoplastic testes [Villagómez et al, 2011], and in 1 case, the gonads were not analysed, however, it was suggested that the mare was affected with an androgen insensitivity syndrome [Switonski et al, 2005]. Thus, an alteration in the function of primary testis-determining genes does not appear to be the cause of these anomalies.…”
Section: Xy Sex Reversal In the Horsementioning
confidence: 99%